Penguatan Protokol Kesehatan COVID-19 Menjelang Pembelajaran Tatap Muka Sekolah Dasar (SD) pada Guru se- Kecamatan Cimalaka - Nunung Siti Sukaesih; Ahmad Purnama Hudaya; Hikmat Pramajati; Popi Sopiah; Emi Lindayani (Jurnal Pengabdian Pada Masyarakat, 2022)
STRENGTHEN THE COVID-19 HEALTH PROTOCOL FOR ELEMENTARY SCHOOL TEACHERS PREPARING FACE-TO-FACE LEARNING. The global health crisis caused by the COVID-19 disease has had an impact on all aspects of life, including education. Approximately 1.3 billion students in 195 countries were affected by the closure of schools in mid-April 2020. School closures were quite effective in preventing the spread of COVID-19, but on the other hand, there were many negative impacts of prolonged online learning. The implementation of health protocols in schools is a very important factor to prevent the transmission of COVID-19 in school clusters. This Community Service Program in the form of strengthens the implementation of Health protocols to prevent the spread of COVID-19 in the school environment when face-to-face schools re-open at the elementary level. This programming method was carried out in September-October 2021, involving the elementary school teachers who held the health promotion school program and the Covid Task Force in each elementary school in one of the districts in West Java, Indonesia. The district has 29 elementary schools with a total number of 316 teachers, which was carried out online in webinars and offline Focus Group discussions (FGDs). The results of the Webinar and FGDs conducted in this activity received a good response from all webinar participants and FGDs participants. The results of the FGDs showed that several problems had to be addressed immediately, namely the lack of training for the COVID-19 task force in the education unit.